2020
DOI: 10.9734/jammr/2020/v32i2430777
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endoscopy in Round Window Identification during Cochlear Implant

Abstract: Aim: To access the usage of the endoscopy in round window (RW) orientation during cochlear implant (CI). Methodology: This was a retrospective case series study done in Otolaryngology Department, Tanta University, Egypt in 2018 and 2019. Inclusion criterion was all cases with CI surgery in which the endoscopy was used to locate the round window (RW) when this was difficult through the transmastoid approach. Results: The total cohort consisted of 13 CI patients in which endoscopy was used. Age mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Electrodes were inserted in the ST under endoscopic guidance. In 93 CI, a PT was performed and the endoscope facilitated recognition and magnification of RW and the electrodes were placed through the facial recess 21–26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrodes were inserted in the ST under endoscopic guidance. In 93 CI, a PT was performed and the endoscope facilitated recognition and magnification of RW and the electrodes were placed through the facial recess 21–26 …”
Section: Resultsmentioning
confidence: 99%
“…In 93 CI, a PT was performed and the endoscope facilitated recognition and magnification of RW and the electrodes were placed through the facial recess. [21][22][23][24][25][26] In 31 CI, the endoscope was used exclusively (without a microscope) throughout the procedure. 27,28 The active electrode was buried in a trough drilled on the wall of the posterior ear canal and obliterated with fascia, soft tissue flap or bone dust.…”
Section: Key Pointsmentioning
confidence: 99%
“…Their results showed that using endoscopic aided cochlear implant improved the identification of round window and reduced the complications, especially in patients with cochlear malformations. Moreover, Fouad et al 12 had another retrospective study describing the role of endoscopy in round window identification in the cochlear implant in 13 patients, and showed that the endoscopy has a great role in the identification of round window in some difficult cases. 12 Chen et al 9 conducted another study about using endoscopy in finding round window membrane in cochlear implant and decided that endoscopy is beneficial for locating it during cochlear implantation surgery, including surgeries for inner ear anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Fouad et al 12 had another retrospective study describing the role of endoscopy in round window identification in the cochlear implant in 13 patients, and showed that the endoscopy has a great role in the identification of round window in some difficult cases. 12 Chen et al 9 conducted another study about using endoscopy in finding round window membrane in cochlear implant and decided that endoscopy is beneficial for locating it during cochlear implantation surgery, including surgeries for inner ear anomalies. Nassif et al 13 discussed the probability of a round window identification through the posterior tympanotomy using rigid endoscopy into eight patients undergoing cochlear implant and concluded that complete endoscopic exposure through the posterior tympanotomy allows identification of the round window niche as well as the direction of the scala tympani.…”
Section: Discussionmentioning
confidence: 99%